Investigating academic dishonesty among Chinese undergraduate students: does gender matter?. Issue 5 (4th July 2018) - Zhang, Yinxia; Yin, Hongbiao; Zheng, Li
Abstract: The high rate of academic dishonesty reported among Chinese college students has created challenges for practitioners in both domestic and Western universities. Following two contrasting yet complementary scholarly approaches, this study explored the relative importance of predictors indicative of students' intention to cheat (moral attitude, subjective norm and penalty enforcement) and of their educational preparedness for academic integrity (integrity engagement) in explaining academic dishonesty, with an emphasis on gender differences. We administered a questionnaire survey to a sample of 2009 Chinese undergraduate students. The results indicated that moral attitude and integrity engagement were the major predictors, that subjective norm accounted for marginal variations of academic dishonesty, and that the influence of penalty enforcement was insignificant. Some gender differences on both the mean score and effect levels of the four predictors were revealed. The effects of grade, year and area of study on academic dishonesty (and particularly their joint effects with gender) were noteworthy. These findings are discussed relative to the results of prior studies and the Chinese context.